Recensiones - de Sebastián, Luis; Mantilla, Sebastián; Aguirre, S. M. (ECA: Estudios Centroamericanos, 1974)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 29, No. 307, 1974: 331-336.